EVALUASI METODE SEVEN JUMP DALAM PEMBELAJARAN TUTORIAL PADA MATA KULIAH ASUHAN KEBIDANAN KEHAMILAN DI PRODI D-III KEBIDANAN BUKITTINGGI POLTEKKES KEMENKES PADANG - Yosi Sefrina, Meilinda Agus, (Menara Ilmu, 2017)
D-III curriculum in 2011 is a competency based curriculum refers to the law No 20 of 2003 on the education system. Student-centered learning that implement PBL (Problem Based Learning), using seven jump methods. Tutor seven jump applying methods still apply teacher-centered learning in small groups. This research aimed to determine the evaluation methods of seven jump student tutorial discussions Diploma III Midwifery Program of Polytechnic Health Ministry of Padang (in Bukittinggi). This research method is descriptive, explorative non experimental included in qualitative design. The Sample are 84 respondents of first year students of Diploma III Midwifery Program of Polytechnic Health Ministry of Padang (in Bukittinggi). Factors studied are the seven jump in the groups, the reasoning process, self directed learning, and the evaluation of seven jump methods. The result showed that 56% of the seven jump process in the groups is good, 53,6% of the reasoning process of seven jump methods is good, 63,1% of self directed learning is low and 63,1% of the evaluation of seven jump methods is satisfied.The result of the research as an input to the policy makersto plan the training on PBL withseven jump tutorial methods on competence-based curriculum correctly. Key words : seven jump, tutorial, problem-based learning, student centered learning